If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-6=6x+8
We move all terms to the left:
9x-6-(6x+8)=0
We get rid of parentheses
9x-6x-8-6=0
We add all the numbers together, and all the variables
3x-14=0
We move all terms containing x to the left, all other terms to the right
3x=14
x=14/3
x=4+2/3
| -3v+4v=-2 | | -4-2x=x+2 | | -14.9j-19.2=-5.3j | | 4+6x=4x+22 | | ∣2x−6∣=4x | | -50x-24x=80+70 | | X+20+4x+90=180 | | 3x+4x=-9x | | 302=8(7x-4)-2 | | 6.5=9.2-0.9x | | -9-3(x-1)=-18 | | 11x-1+8x+1+85=180 | | 3.61+5.9b=7.5b+15.13 | | 2m-10+12=m+20 | | x+19=207 | | 15j-18-16j=j+16 | | -4x-3=-4x-7 | | 5b+15-16b=-12b-4 | | -8(6v-2)+3=259 | | 2(x+60)-((x+50)+60=210 | | -20-4f=16-6f | | 5x-3=-4x-7 | | 10x-3=-4x-7 | | -20d+14=-19d | | 3v-(-35v)=15-9 | | 3x-3=-4x-7 | | 4(6-4m)=120 | | 2c-4;c=5 | | 13c+10=12c-10 | | 3+6b=6b+5 | | -8+3h=2(h–5) | | 2(x+2)=3x-x+3 |